2021
DOI: 10.4081/jphr.2020.1921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disorders among medical students of Umm Al-Qura University, Makkah, Kingdom of Saudi Arabia

Abstract: Background: Sleep disorders are a common medical problem and can affect health and quality of life. There are multiple types of sleep disorders such as obstructive sleep apnea, insomnia, narcolepsy, restless legs/periodic limb movement disorder, circadian rhythm disorders, sleepwalking and nightmares. Medical students appear to be more liable to develop sleep disorders due to their high academic load.Design and Methods: This study seeks to estimate the prevalence of sleep disorders among Umm Al-Qura University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
2
27
0
3
Order By: Relevance
“…According to a regression-analysis we found that the females were 1.67 times higher risk of insomnia as compared to male’s medical clinical students. Our finding was congruent with another study’s findings where female students, were reported to be having insomnia ( Abdelmoaty Goweda et al, 2020 ). Another study reported similar findings as stated that here is a greater risk of stress and insomnia in females compared to male ( Bamuhair et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to a regression-analysis we found that the females were 1.67 times higher risk of insomnia as compared to male’s medical clinical students. Our finding was congruent with another study’s findings where female students, were reported to be having insomnia ( Abdelmoaty Goweda et al, 2020 ). Another study reported similar findings as stated that here is a greater risk of stress and insomnia in females compared to male ( Bamuhair et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…En concordancia a estos datos, un estudio en Arabia Saudita realizado antes del COVID-19 mostró que 77,2% de estudiantes iban a dormir pasada la medianoche 32 . Este retraso en el inicio del sueño se puede relacionar a la alta carga académica, las horas de exposición a pantallas, insomnio y problemas de ansiedad que tuvieron tendencia a aumentar en la coyuntura actual 33 . Además, nuestro estudio revela alta prevalencia de insomnio (60.1%) que se asemeja a lo observado en Marruecos 34 , pero, con amplia diferencia de otro estudio previo a la pandemia (18,3%) 35 .…”
Section: Discussionunclassified
“…During the first semester of 2020, especially during population lockdowns, multiple studies have shown the remarkable impact of COVID-19 pandemic on most lifestyle behaviors of undergraduate students. Thus, significant rates of sleep disturbances have been observed [9,10], as well as decreased physical activity levels and increased sedentary behaviors [9,[11][12][13]. A worsening of nutritional and diet quality was also described [14], although a greater adherence to the Mediterranean diet was observed [15] during confinement.…”
Section: Introductionmentioning
confidence: 99%